Answer:
23.8
Step-by-step explanation:
V = 4/3 π r³
V = 4/3 π (15)³
V = 4500 π
V = 4/3 π r³
4500 π / 2 = 4/3 π r³
1687.5 = r³
r ≈ 11.9
d ≈ 23.8
Answer:
110
Step-by-step explanation:
Let's define
. So when we divide it by 'x+1', we can use Bezout's Theorem which states: that any polynomial(P(X)) divided by another binomial in the form 'x - a', then the remainder will be P(a).
We can use this fact to determine the remainder, because we divided our P(X) by x + 1 which is the same as x - (-1). So we plug in P(-1).
P(-1) = (-1)^11 + 101 = -1 + 101 = 110
Answer:
8+7=21
Step-by-step explanation:
Independent variables are the things that change to see the affect of the dependant variable. In this case, the size of the last meal changes and affects the giraffes hunger level. The size of its last meal is the independent variable.
Answer:
For the first question it is 2.
2 x 2 = 4
5 x 2 = 10
4 + 10 - 14 = 0
The second question is -2
-2 x -2 = 4
5 x -2 = -10
4 + -10 + 6 = 0
Hope this helps
Step-by-step explanation: